2008
DOI: 10.1103/physrevlett.101.137002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pairing above the Transition Temperature of Cuprate Superconductors from the Electronic Dispersion in the Pseudogap Phase

Abstract: In the underdoped high temperature superconductors, instead of a complete Fermi surface above Tc, only disconnected Fermi arcs appear, separated by regions that still exhibit an energy gap. We show that in this pseudogap phase, the energy-momentum relation of electronic excitations near EF behaves like the dispersion of a normal metal on the Fermi arcs, but like that of a superconductor in the gapped regions. We argue that this dichotomy in the dispersion is difficult to reconcile with a competing order parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
122
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 28 publications
20
122
0
Order By: Relevance
“…A particularly interesting case is the cuprate high-temperature superconductors, where the parent and SC phases do not appear to coexist but the phase competition is actually intensified by the emerging of a "strange metal" normal state with pseudogap opening at a temperature T * well above T c in the underdoped regime [5]. The origin of the pseudogap has been controversial, being attributed to preformation of Cooper pairs [16][17][18][19][20][21] or a hidden CO such as d-density wave (DDW) [22][23][24][25][26][27], spin-density wave (SDW) [28][29][30][31], loop-current [32], nematic or stripe order [33][34][35][36][37][38], and pair density wave [39,40], etc. It has been observed that upon doping, T * decreases gradually in the normal state above the T c dome, and enters into the SC dome near the optimal doping level at x OP .…”
Section: Introductionmentioning
confidence: 99%
“…A particularly interesting case is the cuprate high-temperature superconductors, where the parent and SC phases do not appear to coexist but the phase competition is actually intensified by the emerging of a "strange metal" normal state with pseudogap opening at a temperature T * well above T c in the underdoped regime [5]. The origin of the pseudogap has been controversial, being attributed to preformation of Cooper pairs [16][17][18][19][20][21] or a hidden CO such as d-density wave (DDW) [22][23][24][25][26][27], spin-density wave (SDW) [28][29][30][31], loop-current [32], nematic or stripe order [33][34][35][36][37][38], and pair density wave [39,40], etc. It has been observed that upon doping, T * decreases gradually in the normal state above the T c dome, and enters into the SC dome near the optimal doping level at x OP .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental data [10,[27][28][29][30][31][32][33][34][35] provided a rather clear evidence that the critical temperature T c in the underdoped cuprate superconductors (and similarly in the ultracold fermion gasses near the unitary limit [38]) is not related to appearance of the fermion pairs but corresponds to the onset of their phase coherence. Upon approaching T c from above the short-range superconducting correlations gradually emerge.…”
Section: Superconducting Fluctuationsmentioning
confidence: 99%
“…They are mutually coupled through the charge exchange (Andreev-type) scattering. Such scenario (31) has been considered by various authors in the context of high T c superconductivity [14][15][16][17][18][19][20][21] and for description of the resonant Feshbach interaction in the ultracold fermion atom gasses [36][37][38].…”
Section: Superconducting Fluctuationsmentioning
confidence: 99%
“…Above T c , the pseudogap is gradually filling up and remains essentially constant, with a tendency to increase at higher temperature before vanishing at a crossover temperature known as T * . Also some ARPES measuremets seem to provide an evidence for the direct relation between the pseudogap and pairing [25]. In the underdoped compounds, instead of a complete Fermi surface above T c , only disconnected Fermi arcs appear, separated by regions which still exhibit an energy gap.…”
Section: Introductionmentioning
confidence: 99%
“…The term pseudogap has been coined to describe this kind of physics. The presence of pseudogap has been established through the measurements of the nuclear magnetic resonance (NMR) [5], the scanning tunneling spectroscopy [6][7][8][9], the analysis of the electronic Raman scattering [10][11][12], through time-resolved optical spectroscopy [13][14][15][16][17][18], and through the ARPES [19][20][21][22][23][24][25]. The observed strong Nernst effect in cuprates has been also attributed to it [26][27][28].…”
Section: Introductionmentioning
confidence: 99%